(untitled) (KONFERENSIYA, 2025)
This article examines rhetorical features in the professional speech of English and Uzbek pedagogical workers through the lens of linguoculturology. It explores how cultural values, national communicative traditions, and educational ideologies shape teachers’ rhetorical strategies. The study compares persuasive, expressive, and interactional rhetorical patterns in both linguistic communities, highlighting their sociolinguistic motivations and pedagogical implications. The findings demonstrate that rhetoric in teacher speech functions not only as a communicative tool but also as a cultural embodiment of identity and pedagogical authority.